Enhancing 5th-Grade Student Learning Outcomes with the Predict-Observe-Explain Learning Model in Integrated Thematic Learning - Budi, Ragil Setia; Mardati, Asih (The Indonesian Institute of Science and Technology Research, 2024)
The Curriculum 2013 for elementary schools is designed around integrated thematic learning, One such approach is the Predict-Observe-Explain (POE) model. This study investigates the impact of the POE learning model on the learning outcomes at a private elementary school. Employing a quantitative experimental method with a Quasi-Experimental Design, the research targets fifth-grade students as the population. The independent variable is the learning model, while the dependent variable is the student's learning outcomes in integrated thematic learning. Data were collected through observation, tests, and documentation. The findings reveal a significant positive effect of the POE learning model on student learning outcomes. This is demonstrated by an increase in the average post-test scores compared to pre-test scores by 10.05, verified using the Wilcoxon test. Additionally, the Mann-Whitney U test analysis shows a significance value of 0.002, which is less than the alpha value of 0.05. This indicates a significant difference in learning outcomes between the experimental and control groups, confirming the effectiveness of the POE learning model in enhancing student learning in integrated thematic contexts.